Impact of Stray Animals on Road Safety: A Case Study of the East-West Highway Section in Bheemdatta Municipality Area, Nepal - Khadka, Rabin; Negi, Crimsan S; Khatri, Madhavi; Pali, Puja; Dhanadi, Shristi; Bhatta, Kishan Datta; Bhatt, Toran Pd; Bhatta, Youb Raj (Journal of Engineering Technology and Planning, 2025)
This research aims to assess the impact of stray animals on traffic safety in the Bheemdatta Municipality region along the East-West Highway section. Over the past seven years, the frequency of road accidents involving stray animals has escalated, resulting in increased animal-vehicle collisions, fatalities, and significant financial damages. A mixed-method approach was adopted, combining both quantitative and qualitative methods, with data analyzed using descriptive statistics and statistical charts. Data was collected from local traffic police records over the past three years, along with questionnaire surveys conducted with 154 respondents, including drivers, passengers, residents, and traffic police. The findings revealed 13 recorded animal-vehicle collisions, with 5 human deaths, 9 stray animal injuries, and 13 stray animal deaths. Additionally, 92.2% of respondents reported encountering stray animals on the roads daily. The study suggests that measures such as using reflective collars, enforcing animal ownership laws, and establishing shelters for stray animals, along with utilizing stray animals for biogas production, could reduce the adverse impact on road safety. This research underscores the need for effective animal management strategies along with sustainable solutions to enhance road safety and protect both human lives and the welfare of stray animals in the region.